EFFECT OF PRE - PROCESSING ICED STORAGE ON DETERIORATIVE CHANGES IN LIPIDS OF SILVER POMFRET STORED AT -18 C - SANKAR, T V; NAIR, P. G VISWANATHAN (Fishery Technology, 2017)
Silver pomfret (Parnpus argenteus) was frozen in the fresh condition as well as after holding in ice for one, two and four days. Evaluation of changes is the quality of these samples during storage at â€” 18Â°C has shown that shelf-life decreased sharply if the pre-freezing iced storage was more than one day. The shelf-life of one day iced, two day iced and four day iced frozen samples were 32, 20 and 16 weeks respectively.No correlation was observed between the peroxide value and the organoleptic detection of rancid flavour. Levels of free fatty acids were more in the samples frozen after storage in ice for one day than in all the other samples.